Pengaruh Budaya Organisasi Dan Penilaian Prestasi Kerja Terhadap Pengembangan Karir Divisi Surveyor Kjpp Di Jakarta Selatan - Siti Hanifatul Fauziah; Esti Suntari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the influence of the relationship between organizational culture and work performance assessment in supporting career development in the Surveyor Division at KJJP South Jakarta. The method used is quantitative research with a descriptive approach. The sampling technique was partial and simultaneous using accidental sampling. The data collection technique in this study used a questionnaire and obtained a sample of 84 respondents. Data analysis used the SPSS version 26 program. The analysis techniques used were validity test, reliability test, classical assumption test, regression analysis, coefficient of determination and hypothesis test. The results of this study are that Organizational Culture has no significant effect on Career Development with the hypothesis test obtained t count < t table or (0.270 < 1.664) with a significance value (0.788 > 0.05). Work Performance has a significant effect on Career Development with the hypothesis test obtained t count > t table or (2.998 > 1.664) with a significance value (0.004 < 0.05). Organizational Culture and Job Performance simultaneously have a significant effect on Career Development, with the regression equation Ŷ = 13.781 + 0.050X1 + 0.588X2 + e, and a correlation value of 0.598. The coefficient of determination is 0.358, or 35.8%, while the remaining 64.2% is explained by other factors. Hypothesis testing yielded a calculated F value > F table, or (22.575 > 3.109).